2020
DOI: 10.1186/s12891-020-03372-5
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of surgical site infection may be related to suboptimal case selection for non-selective arterial embolization during resuscitation of patients with pelvic fractures: a retrospective study

Abstract: Background: In most institutions, arterial embolization (AE) remains a standard procedure to achieve hemostasis during the resuscitation of patients with pelvic fractures. However, the actual benefits of AE are controversial. In this study, we aimed to explore AE-related outcomes following resuscitation at our center and to assess the predictive value of contrast extravasation (CE) during computed tomography (CT) for patients with hemodynamically unstable closed pelvic fractures. Methods: We retrospectively re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Selective or super-selective embolization was performed in a branch of the internal iliac artery for the remaining four patients. One study demonstrated nonselective angioembolization as one of the risk factors for SSI [ 27 ]. Burlew et al [ 6 ] suggested that empiric embolization of both internal iliac arteries should be carefully weighed against the risks of pelvic claudication and perineal necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Selective or super-selective embolization was performed in a branch of the internal iliac artery for the remaining four patients. One study demonstrated nonselective angioembolization as one of the risk factors for SSI [ 27 ]. Burlew et al [ 6 ] suggested that empiric embolization of both internal iliac arteries should be carefully weighed against the risks of pelvic claudication and perineal necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to comment on the article “High incidence of surgical site infection may be related to suboptimal case selection for non-selective arterial embolization during resuscitation of patients with pelvic fractures: a retrospective study” by Lai et al [ 1 ], which was recently published in BMC musculoskeletal disorders.…”
Section: Main Textmentioning
confidence: 99%
“…Pelvic fractures account for 1%-3% of all skeletal injuries, and the management remains challenging for orthopedic surgeons [1]. Significant functional morbidities and a relatively high rate of mortality, ranging from 10 to 16%, may be hypothetically associated with pelvic fractures [2][3][4]. Therefore, optimal treatment methods to save lives and preserve a satisfactory functional status in patients, following pelvic fracture, are being developed.…”
Section: Introductionmentioning
confidence: 99%